La giusta narrazione. Il bisogno di riconoscimento nella società tecnologica - Beltramo, Giorgio Lorenzo (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2023)
The human need for recognition unites the thoughts of Fabietti, Remotti and Augé in anthropology, albeit in their specificities. Having delineated a figure of the concept, also through comparison with the philosophical thought of Honneth, its conditions of possibility in the juridical-technological society are investigated. Narrative, among the five components of the conceptual figure identified, appears decisive in the human search for recognition. It is therefore chosen here as the preferred perspective for looking at the normative environment in which humans are immersed.